Intensity and chronology of pre-breeding and post-breeding moult in White-faced Whistling-ducks Dendrocygna viduata - Petrie, Scott A (Wildfowl, 1998)
The intensity and chronology of moult in breeding and post-breeding White-faced Whistling- Ducks Dendrocygna viduata were studied during 1992/1993 and 1995 in a semi-arid region of Northern Province, South Africa. Adult males and females were moulting in most feather areas when they arrived on the breeding grounds in December and January and continued to do so during rapid follicular growth. Both sexes moulted at a very low intensity during reproduction, males had a higher moult intensity score than females during both laying (P=0.04) and incubation (P=0.002). Contour-feather replacement peaked during brood rearing and pre-wing moult and was followed by loss of primaries and secondaries. Most feather areas were moulting intensively during the latter stages of wing-feather growth and continued to do so after birds had regained flight capability. The ephemeral nature of breeding habitats in southern Africa may have selected for the retention of winged feathers by brood rearing adults, as well as flexibility in the timing and location of wing-moult. While White-faced Whistling-Ducks replace contour feathers during brood rearing, the low protein content of their diet and high nutrient costs associated with reproduction apparently necessitate the separation of intense feather replacement and both laying and incubation. Their single annual moult and lack of a breeding plumage permits White-faced Whistling-Ducks to initiate breeding whenever suitable habitats become available and enables them to prolong moult over a large portion of the annual cycle. Shared costs of incubation and brood rearing, perennial monogamy and lack of a breeding plumage could be the selection pressures leading to somewhat similar inter-sexual moult patterns and intensities.